2021
DOI: 10.3928/23258160-20210528-02
|View full text |Cite
|
Sign up to set email alerts
|

Should We Stop Treating Patients With Eplerenone for Chronic CSCR? Commentary on the VICI Trial

Abstract: The VICI trial reported by Lotery et al. is a recent placebo-controlled, randomized trial that examined the efficacy of eplerenone treatment for chronic central serous chorioretinopathy (CSCR) in 104 patients. The study found no significant difference in best-corrected visual acuity (BCVA) between the eplerenone-treated and placebo groups, prompting the VICI investigators to conclude that eplerenone should not be prescribed to treat CSCR. Limitations of the study include the patients' high baseline BCVA, use o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…It has been reported that there is no difference in final visual acuity between cases where intravitreal anti-VEGF injection was not performed when the SRF was < 200 μm and cases where additional injections were performed whenever SRF was detected in patients with neovascular age-related macular degeneration [22]. In addition, Daugirdas et al [23] pointed out that, in an RCT study published in 2020 [17], only the SRF of one cross-section was measured and compared, and the results may be different when comparing SRF volumes. What should be noted here is the fact that SRF decreased significantly compared to baseline in the eplerenone group.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that there is no difference in final visual acuity between cases where intravitreal anti-VEGF injection was not performed when the SRF was < 200 μm and cases where additional injections were performed whenever SRF was detected in patients with neovascular age-related macular degeneration [22]. In addition, Daugirdas et al [23] pointed out that, in an RCT study published in 2020 [17], only the SRF of one cross-section was measured and compared, and the results may be different when comparing SRF volumes. What should be noted here is the fact that SRF decreased significantly compared to baseline in the eplerenone group.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, some argue against the recommendation of discontinuation of eplerenone, particularly given that the drug is well-tolerated by most. 56,57 A subsequent meta-analysis including the VICI trial demonstrated no superiority of MRAs at months 1 through 6 in terms of BCVA outcomes, but did find that MRAs were associated with decreases in subfoveal choroidal thickness, SRF, and CMT when data were pooled. 58 ' Intravitreal anti-VEGF Based on the success of intravitreal anti-VEGF drugs in the treatment of other retinal diseases over recent years, attempts to translate this success to CSCR have been made with mixed results.…”
Section: Non-pdt Laser Therapymentioning
confidence: 99%
“…56 In addition, clinical experience has also demonstrated a rebound effect of fluid upon eplerenone discontinuation. 57 VICI trial patients discontinued treatment as soon as SRF resolved causing 30% of patients to receive eplerenone for less than 3 months which may have negatively affected observed efficacy. 56 Further arguments include that a greater percentage of PDT treatment occurred in the placebo group and that the study's anatomic outcomes focused on SRF thickness instead of volume.…”
Section: Non-pdt Laser Therapymentioning
confidence: 99%
See 2 more Smart Citations